Altitude Pulmonary Edema or Altitude Disease - Amilcar Tinoco Solórzano (Universidad de las Ciencias Médicas de Cienfuegos, 2018)
Hypobaric hypoxia caused by the decrease of partial environmental oxygen pressure associated to the barometric pressure drop, secondary to altitude increase, meets the criteria of causal agent of altitude disease caused by non-acclimation to altitude. Its incidence and severity are related to individual susceptibility. Severe altitude disease is characterized by the inability to do daily activities, non-carcinogenic acute edema, dehydration and hypothermia.